The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bjhh.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

De novo alpha 2 hemoglobin gene (HBA2) mutation in a child with hemoglobin M Iwate and symptomatic methemoglobinemia since birth

Abstract: Cyanosis in an apparently healthy newborn baby may be caused by hemoglobin variants associated with the formation of methemoglobin, collectively known as M hemoglobins. They should not be confused with genetic alterations in methemoglobin reductase enzyme systems of red cells since treatment and prognosis are completely different. A newborn male child was noted to be significantly cyanotic at birth and is the basis for this report. Hemoglobin isoelectric focusing, acid and alkaline gel electrophoresis, and HBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Since chemical characterizations of Hb M were first reported in the late 1950s and early 1960s by Gerald [6, 7], the rare globin chain variants have been investigated by chromatography, electrophoresis, and gene sequencing [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since chemical characterizations of Hb M were first reported in the late 1950s and early 1960s by Gerald [6, 7], the rare globin chain variants have been investigated by chromatography, electrophoresis, and gene sequencing [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Hb M caused by a mutation in α-, β-, or γ-globin can lead to spontaneous oxidation of the ferrous ion in the heme and cannot transport or release oxygen in tissues. Hb M disease causes cyanosis that is unresponsive to oxygen therapy [1, 2]. Some variants might need to be considered in the differential diagnosis of central cyanosis in newborns because they cause cyanosis from birth.…”
Section: Introductionmentioning
confidence: 99%
“…It was first characterized in the Iwate prefecture of Japan in 1960 where terms like 'black mouth', 'black blood' or 'black child' were used historically to denote the cyanosis in these individuals [2,8,9]. A few case reports have subsequently also been published from Europe [10,11,12], Turkey [13] and Brazil [14]. Hb M-Iwate was previously also christened as Hb M-Oldenburg, M-Kankakee and M-Sendai, all of which after molecular characterization were found to be the same variant [4,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, it was discovered that mutation of the R671 residue (that modulates the activity of early tryptic fragmentation) alters the conformation of the calcium pumps of SERCA 3 (Corvazier et al, 2009). In the haemoglobin molecule, genetic variants have been reported that cause cyanosis (a diminution in oxygen affinity) when the H58 residue is mutated (a variant known as Hb M Boston) (Nishikura et al, 1975;Viana and Belisário, 2014). Similarly, a further variant known as Hb Hornchurch shows a mutation in the E43 residue, which may be related to diminution in the plate count (thrombocytopenia) (Shi and Wang, 2017).…”
Section: Signal Transduction In Other Receptor-ligand Systemsmentioning
confidence: 99%